English Literature in English Medium Schools in Bangladesh: The Question of Post-colonial Pedagogy - Al-Quaderi, University of Dhaka, Bangladesh, Golam Gaus; Al Mahmud, United International University, Bangladesh, Abdullah (Asiatic: IIUM Journal of English Language and Literature, 2010)
English literature has been part of the syllabus of English-medium schools from the early days of the British colonial encroachment in the South Asian region. In today’s Bangladesh from the late seventies, the O/A level or equivalent â€œinternationalâ€ systems started spreading, instead of the â€œnational curriculum in English-mediumâ€ of the Pakistani era. The proliferation of English-medium schools after 1990, concurrent with the wholesale adoption of free market policies, the return of democracy in 1990, and globalisation, has meant that an ever-increasing number of Bangladeshi children and young adults are studying English literature as a compulsory subject until standard eight, or as an optional subject after that. However, they are doing this in an inchoate way, some if not many of them imbibing the inherent culture, values and worldviews of these texts. The students remain comparatively unaware of other non-western literatures, including to some extent, Bengali literature, due to the primacy of English language, literature and culture in these institutions. Thus, there is a need for a postcolonial pedagogic system for English literature at these institutions in order to offset the effects of neo-colonialism. This study tries to analyse the present teaching and learning practices, argues for a post-colonial pedagogy and suggests ways of formulating a revised pedagogy for teaching English literature at these schools.